2022
DOI: 10.1186/s12896-022-00762-6
|View full text |Cite
|
Sign up to set email alerts
|

Gene cloning and molecular characterization of a thermostable chitosanase from Bacillus cereus TY24

Abstract: Background An important conceptual advance in health and the environment has been recognized that enzymes play a key role in the green processing industries. Of particular interest, chitosanase is beneficial for recycling the chitosan resource and producing chitosan oligosaccharides. Also, chitosan gene expression and molecular characterization will promote understanding of the biological function of bacterial chitosanase as well as explore chitosanase for utilizing chitosan resources. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…1% yeast extract proved to be the best nitrogen source for B44 38 , which exactly matched Zhang et al, 2022. Among the nitrogen sources, peptone, yeast extract, and ammonium chloride were shown to influence the growth of organisms, whereas the growth of the organisms ceased with urea-added production media 39 . The nitrogen sources in our present optimization study revealed that strain B44 utilized peptone (0.5%) and ammonium chloride (0.5%) for the highest activity.…”
Section: Fig 4: Effect Of Ph On Fig 5: Effect Of Temperature Chitosan...mentioning
confidence: 99%
“…1% yeast extract proved to be the best nitrogen source for B44 38 , which exactly matched Zhang et al, 2022. Among the nitrogen sources, peptone, yeast extract, and ammonium chloride were shown to influence the growth of organisms, whereas the growth of the organisms ceased with urea-added production media 39 . The nitrogen sources in our present optimization study revealed that strain B44 utilized peptone (0.5%) and ammonium chloride (0.5%) for the highest activity.…”
Section: Fig 4: Effect Of Ph On Fig 5: Effect Of Temperature Chitosan...mentioning
confidence: 99%